Efektivitas Pembelajaran Ekonomi Pada Materi Circular Flow Diagram dengan Menggunakan Media LED Meteor di Kelas X3 SMAN 2 Rambatan - Fitriany Febby Adiana Gustariny (Warta Pendidikan | e-Journal, 2021)
Economy learning, specifically for Circullar Flow Diagram, is like a sketsa or scema that explain about the flow of production factors and income flow happened in market input, as well as flow of goods and money that occured at the market output. Generally, the flows are simbolized with arrow signs. Based on continous teaching experience, these medias of teaching are not interesting to the students, and also it hard for the to understand. As the result the learning activities will no be effective. Moreover, the writer think of how the flows stated in the arrow signs to be really seen in moving. To show these moving flows the writer use Led Meteor medias. Hopefully, by applying these medias, learning process will be more interesting and meaningful because knowledge that they get come from their experience themselves. This process will also help student to understand and to make learning more effective. From the result research obtained average result % learning efektivenes at 1st Cycle as 59,50 (Enough) and 2nd Cycle as 80,22 (Very Good) and there is an increasement % learning efektivenes from 1st cycle to 2nd cycle as 20,70.